Implications of the timing of residential natural gas use for appliance electrification efforts - Eric Daniel Fournier; Robert Cudd; Felicia Federico; Stephanie Pincetl (Environmental Research Letters, 2020)
Current strategies for deep decarbonization of the residential building sector invoke the following three pillars of action: (1) radically improve the efficiency of end-use electricity consumption, (2) shift to 100% renewable generation of electrical grid power, and (3) move aggressively to electrify all remaining fossil fuel end-uses. Due to the previous unavailability of high temporal resolution natural gas consumption data, the pursuit of this policy agenda has largely occurred in the absence of a thorough understanding of hourly variations in the intensity of household natural gas use. These variations can have important downstream impacts on the electricity system once electrification has been achieved. This study presents a series of analyses which are based upon a novel dataset of hourly interval natural consumption data obtained for (N = 17,072) households located within a low-income portion of Southern California Gas Company’s service territory. Results indicate that diurnal patterns of hourly natural gas use largely coincide with the timing of daily peak electricity loads. These findings suggest that the aggressive electrification of residential end-use appliances has the potential to exacerbate daily peak electricity demand, increase total household expenditures on energy, and, in the absence of a fully decarbonized electrical grid, likely result in only limited greenhouse gas emissions abatement benefits.